Faktor yang Mempengaruhi Kepuasan Wisatawan Berkunjung di Serangan Denpasar Bali - Satia Negara, I Made Weda; Sudiarta, I Nyoman; Suardana, I Wayan (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019DO - 10.24843/JUMPA.2019.v06.i01.p07, 2019)
Serangan located in South Denpasar is a tourist destination, visited by many foreign and domestic tourists. The purpose of this study is to determine the characteristics of tourists and seeking the dominant factors affecting the satisfaction of tourists visiting tourist attractions in Serangan. This study uses a survey research design with a sample of 180 respondents. By using a factor analysis technique and processed using the IBM SPSS version 23. The results of the factor analysis have been identified that there are six factors form the satisfaction of tourists visiting tourist attractions in Serangan. First Factors include the beach, the attractive scenery , the peace and quiet and the tourist attraction factor. Factors 2 namely, hygiene, cultural activity, sports activity and information factors. Factors 3 namely, weather, food and cost factor. Factors 4 encompass lodging, historical place, attractive village and access factor. Factors 5 are the boat service and the local community life factor. Factor 6 is safety. From these 6 groups of factors found that the most dominant is beach factor which has influenced the satisfaction of tourists visiting tourist attractions in Serangan. Based on the findings of this study, it is hope that the government preserves the main factors forming the satisfaction of tourists who visit the tourist attraction in Serangan island. Keywords: Satisfaction, Attraction, Tourists, Serangan.